‘Health Camp’ model: a unique approach for child vaccination in non-state armed actor controlled, inaccessible geographies in Somalia - Mohamed Hussein Kahow; Salad Ahmed Halane; Asma Ali; Rashed Shah (Global Health Action)
Decades of conflict, political instability, and limited infrastructure left Somalia facing significant challenges to offer consistent and equitable health services, especially for child vaccination. Recent data reveals alarming vaccination gaps, with 60% of children receiving no vaccinations, and only 11% completing required vaccines. Despite global support, an estimated 1.15 million children remain unvaccinated, half of them reside in inaccessible areas controlled by non-state armed actors. In this context, the Far-Reaching Integrated Delivery (FARID) project was initiated since October 2022 across 10 districts of Galmudug and Hirshabelle state in Somalia. Employing the ‘Health Camp’ model, FARID addresses social, structural, and gender barriers, adapting to ever-changing context of inaccessible regions by providing mobile health facilities and outreach health and nutrition services, including child vaccination. This approach effectively reached previously unreached population in Somalia’s most difficult-to-reach areas. Implemented in phases, the project immunized 51,168 children (0–23 months) who had not received any prior vaccinations (23,753 boys and 27,415 girls), screened and treated 14,158 malnourished children (0–59 months) and vaccinated 11,672 pregnant women during March–December 2023. The project’s success hinges on intensive community engagement, local partnerships, innovation in mapping and data management, and delivery of integrated services tailored to population needs. The project underscores the critical role of local community-based organizations and clan elders in reaching inaccessible populations through humanitarian negotiation amidst security challenges. The project has achieved significant milestones aligned with national health strategic plans, including progress towards universal health coverage and improved immunization access in Somalia’s most challenging regions.